ESTIMASI STOK KARBON MANGROVE DI MUARA SUNGAI KUMBE DISTRIK MALIND KABUPATEN MERAUKE - Reny Sianturi; Siti Masiyah (Musamus Fisheries and Marine Journal, 2018)
Forests reduce and store CO2 through a process of "sequestration" that is the storage of carbon from the atmosphere and its storage in several copartments such as plants, litter, and soil organic matter. Mangrove forest is a unique and unique type of forest because it is able to adapt to environments with high salinity, soil conditions without oxygen and once in a while. ne example of mangrove forests in Indonesia is mangrove forest in the Kumbe river estuary, Merauke Regency, Papua Province. The Kumbe river estuary is one of the eastern Indonesian waters bordering the Indian Ocean. At the Kumbe river estuary there has been no research on carbon stocks in the mangrove community. So it is necessary to do research on carbon stocks in the region. In this study the measurement of carbon stocks used was done by measuring carbon above ground, and ground. Above ground carbon stock components include trees, understorey, and litter. The mechanism for measuring above ground carbon stock is done by estimating biomass, which is then converted to carbon concentration. The results of this study indicate that the carbon stocks in trees, Understorey and litter in sequence are 85.55 Mg / Ha, 392.93 Mg / Ha and 70.75 Mg / Ha; 0.78 Mg / Ha, 1.26 Mg / Ha and 1.24 Mg / Ha and 2.04 Mg / Ha, 1.28 Mg / Ha and 1.2 Mg / Ha. As for the proportion of carbon stock values ​​found in mangrove forests that trees contribute greatly to total carbon stock. Keyword : Mangrove, carbon stocks, Merauke, Kumbe